The use of grammar translation method in teaching English - Catharina Elmayantie (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2015)
This study aims to describe the patterns of Grammar Translation Method (GTM) and to know the reasons why the teachers used the method. Descriptive qualitative method was applied. The subjects were two English teachers at the seventh grade of SMP Negeri 1 Palangka Raya. It was used observation and questionnaires to collect the data. The data reduction, data display, and conclusion drawing were applied for data analysis. The findings show nine major patterns of GTM applied: (1) The classes were taught mainly in mother tongue; (2) the vocabulary was taught in the form of lists of isolated words; (3) the grammar provided the rules for putting words together; (4) it focused on the form and inflection of words; (5) the reading difficult classical texts were begun early; (6) it was little attention to the content of the texts; (7) the drills were exercises in translating; (8) it was little attention to pronunciation; and (9) it focused on accuracy. Meanwhile, the reasons of the teachers used the method are: (1) It is suitable for the students; (2) it helps the students comprehend the text; (3) it improves the vacabulary; and (4) by using this method teaching-learning activities work well.